(untitled) (Innovative professional education, 2025)
The article defines the features, characteristics, and conditions for applying the project method in the development of professional competence of teachers of a vocational college. The structure of the project learning technology is proposed, consisting of three stages (project launch; implementation; defense) and nine stages that reflect the components of real research activities. The conclusion is made about the feasibility of organizing training sessions for the development of innovative knowledge, skills, and abilities among teachers